Mathematics Education in Sub-Saharan Africa : Status, Challenges, and Opportunities - Bethell, George (World Bank, Washington, DC, 2016)
This study on Assessment of mathematics education in Sub Saharan African countries is in support of the efforts to improve mathematics education in the countries of Sub-Saharan Africa (SSA). The study is in response to a growing recognition that countries in SSA will need to boost performance in the Science Technology, Engineering and Mathematics (STEM) subjects if they are to realize their full potential in a competitive global market increasingly shaped by the use of new technologies. Chapter 1 of this report lists the constituent countries of SSA and describes the study’s research questions and methods. Chapter 2 explores the economic and social arguments for making the improvement of mathematics education in the region a priority. Chapter 3 presents evidence as to current levels of numeracy and mathematical competence in the countries of SSA from a wide range of assessments. Chapter 4 looks at factors which have the potential to raise mathematical achievement indirectly by improving the quality of schooling in general. Chapter 5 considers the effectiveness of various interventions targeted specifically at improving mathematical outcomes. Chapter 6 and Chapter 7 are dedicated to issues concerning the capacities of serving teachers of mathematics and the pre-service training arrangements for those preparing to teach mathematics in schools. Chapter 8 describes assessment practices and their potential roles in improving learning outcomes. Chapter 9 gives an overview of a range of more recent initiatives designed to improve mathematics education both in SSA and beyond. Chapter 10 summarizes the study’s main findings and sets out some suggestions for overcoming barriers to progress. Finally, Appendix A sets out the findings of the in-country surveys.